A first approach to the Design Component in the agri-food industry of southern Spain - González-Yebra, Óscar; Aguilar, Manuel A.; Aguilar, Fernando J. (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2019)
This work raises the need to open new research lines to bring closer "Design" and "Agri-food Industry", understanding design as a structured and multidisciplinary working process headed up to create products, images, spaces, etc. Within this framework, the following objectives have been outlined: i) Identification of the major design areas with regards to the agri-food sector, ii) estimation of the importance of the "Design" component and iii) definition of the possible lines of action. After carrying out a previous bibliometric analysis, which highlighted the lack of relevant bibliography regarding the design component in the agri-food sector, the Delphi method was selected as a suitable working methodology to interactively and systematically answer the aforementioned questions by relying on a panel of experts. The obtained results pointed out to the need of providing incentives for design in agri-food industry as a non-technological innovation aimed at increasing the added value and development of the sector. This should also help promote the design culture and push forward the creation of innovative business strategies.